Síndrome da deleção 22q11.2: impacto da deleção na expressão gênica e o papel do gene tbx1 na formação cardíaca em um modelo animal. - Dantas, Anelisa Gollo [UNIFESP] (2019)
The 22q11.2 deletion syndrome (22q11.2DS) results from the loss of a ~3 Mb segment of chromosome 22. The syndrome is characterized by a broad phenotypic spectrum, and the most debilitating clinical signs are psychiatric disorders, immunological deficiency, and mainly congenital heart diseases. Little is known about the role of the 22q11.2 region genes in the phenotype since it varies even among individuals with deletions of similar sizes. On this way, genetic factors lying outside the deleted region may also play a role in the phenotype. In the present work, different research approaches were used to better understand the genetic mechanisms of the syndrome. The evaluation of the transcriptome of patients with 22q11.2DS and control subjects allowed us to identify gene expression alteration of the hemizygous genes, as well as of genes neighboring the deleted region, and of genes mapped on other chromosomes. These findings showed that the deletion may be capable of disrupting the genomic architecture, which results in the gene regulation alteration, even though the gene has a normal copy number. Another aspect studied was the role of the TBX1 (T-box transcription factor) gene, considered to be the most important gene for cardiac morphogenesis among all genes mapped in the 3 Mb region in 22q11.2. The assay for transposase-accessible chromatin with high throughput sequencing (ATAC-seq) was performed in the embryonic pharyngeal apparatus of mice obtained from Tbx1 transgenic lines, in which the Cre-LoxP recombination system was used for the activation of the green fluorescent protein (GFP) reporter in cells expressing Tbx1. It was possible to observe that the biological processes identified in the population of cells expressing Tbx1 were closely related to cardiac morphogenesis, whereas those processes observed in the cells that did not express Tbx1 were distinct, such as kidney development. In the cell population in which there were overlapping genomic regions identified in both Tbx1-expressing and non-expressing cells, biological processes of general cell maintenance were observed, such as the negative regulation of gene expression. Furthermore, the regulatory regions identified by the methodology presented overlaps with histone modifications frequently observed in promoter and enhancer regions. This strategy facilitates the identification of targets for functional studies as well as help to understand the mechanisms of gene regulation that occur during embryonic development.